TINJAUAN YURIDIS TENTANG KEWENANGAN PEMERINTAH PROVINSI DALAM PENERBITAN IZIN USAHA PERTAMBANGAN BATUBARA - Lathif, Nazaruddin (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
The issuance of licences and nonmetallic minerals and rocks is a form of implementation of the Division of authority between the Government, the Government of the province that is contained in the provisions of article 37 (a) Law No. 4 of the year 2009 Mineral and coal mining.The issuance of licences and nonmetallic minerals and rocks by the Governor also pointed out the existence of a connection between a Government with its citizens in the context of the public service. Before discharge Act No. 4 of the year 2009 about Mineral and Coal Mining permissions settings using the coal law number 11 Year 1967 concerning the provisions of principal mining and also use Regulations The Government's number 32 year 1969 about the Regulations Implementing the provisions of principal mining. The basis of the authority of the provincial government in the coal-mining permit issuance can be outlined as follows: after discharge of Act No. 4 of the year 2009 about Mineral and coal mining permits against providing minerals and coal in the District/City, however, since the publication of the Act No. 23-year 2014 about local governance 2 October 2014 the entire mining activities move from District/City Government to the provincial governments except Coal mining concessions of the Works agreement (PKP2B), Foreign Investment (PMA) and the permissions that are bordered in two or more provinces.